Approach to the Patient: Theranostics as precision medicine for neuroendocrine tumors - Regina Koch; Guillaume Pegna; Nadine Mallak; Celeste Winters; Jaydi Del Rivero; Hallbera Gudmundsdottir; Thor Halfdanarson; Erik Mittra (The Journal of Clinical Endocrinology & Metabolism, 2026)
Abstract Context Theranostics has emerged as a precision medicine paradigm in neuroendocrine tumors (NETs), integrating receptor-based imaging with targeted radionuclide therapy to individualize treatment. This approach is particularly valuable in functional and biologically heterogeneous NETs, where hormonal control and variable clinical behavior dominate therapeutic priorities. Case Description We present a three-case series illustrating the application of theranostics across diverse NET contexts. Case 1 describes a patient with metastatic insulinoma with refractory hypoglycemia, in whom multimodal therapy, including locoregional intervention, was sequenced to prioritize hormonal control, with somatostatin receptor (SSTR) imaging ultimately enabling peptide receptor radionuclide therapy (PRRT) and durable glycemic response. Case 2 discusses a patient with metastatic pancreatic NET who, after prior benefit from PRRT, underwent successful retreatment guided by persistent SSTR expression and appropriate clinical selection, with individualized dosimetry used to optimize safety and efficacy. Case 3 describes metastatic small-intestinal NET grade 3 with carcinoid syndrome, where dual-tracer PET (SSTR and FDG) revealed biologic heterogeneity that informed sequencing of systemic and locoregional therapies alongside PRRT, in the setting of competing priorities including carcinoid heart disease. Conclusions These cases highlight theranostics as a clinical framework that integrates tumor biology, functional imaging, and patient-specific priorities to guide management of NETs. Optimal care requires multidisciplinary coordination across endocrinology, oncology, nuclear medicine, and interventional and surgical specialties, particularly when hormonal morbidity and tumor progression compete in driving treatment decisions. Receptor-based imaging identifies candidates for targeted therapies and provides insight into tumor behavior, enabling sequencing of systemic and locoregional interventions to achieve biochemical and oncologic control.